Development of an optimization model for scheduling, assignment and sequencing of hollow fiber membrane production - Ghashami, Seyed Sajad, 1988-; Wong, Kuan Yew, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2013